Systematics of the Neotropical genus Catharylla Zeller (Lepidoptera, Pyralidae s. l., Crambinae) - Theo Leger; Bernard Landry; Matthias Nuss; Richard Mally; Richard Mally (ZooKeys, 2014)
The Neotropical genus Catharylla Zeller, 1863 (type species: Crambus tenellus Zeller, 1839) is redescribed. Catharylla contiguella Zeller, 1872, C. interrupta Zeller, 1866 and Myelois sericina Zeller, 1881, included by Munroe (1995) in Catharylla, are moved to Argyria Hübner. Catharylla paulella Schaus, 1922 and C.tenellus (Zeller, 1839) are redescribed. Six new species are described by Léger and Landry: C. bijuga, C.chelicerata, C. coronata, C. gigantea, C. mayrabonillae and C. serrabonita. The phylogenetic relationships were investigated using morphological as well as molecular data (COI, wingless, EF-1α genes). The median and subterminal transverse lines of the forewing as well as the short anterior and posterior apophyses of the female genitalia are characteristic of the genus. The monophyly of Catharylla was recovered in all phylogenetic analyses of the molecular and the combined datasets, with three morphological apomorphies highlighted. Phylogenetic analyses of the morphology of the two sexes recovered three separate species groups within Catharylla: the chelicerata, the mayrabonillae, and the tenellus species groups. The possible position of Micrelephas Schaus, 1922 as sister to Catharylla, based on both morphological and molecular data, and the status of tribe Argyriini are discussed. The biogeographical data indicate that the chelicerata species group is restricted to the Guyanas and the Amazonian regions whereas the tenellus group is restricted to the Atlantic Forest in the South-Eastern part of Brazil. The mayrabonillae group is widespread from Costa Rica to South Bolivia with an allopatric distribution of the two species. COI barcode sequences indicate relatively strong divergence within C. bijuga, C. mayrabonillae, C. serrabonita and C. tenellus.